Dukungan Keluarga dan Dampaknya terhadap Tingkat Stres Pasien Diabetes Tipe II di Poli dalam RSUD Bayu Asih - Ahmad Mumtaz Tauba; Alfian Sujatmiko; Andri Nurmansyah (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Background. Family support is a form of interpersonal relationship that includes informational support, instrumental support, emotional support, and companionship. Insufficient family support can lead to a decline in quality of life, one of which is due to psychological issues such as stress. Objectives. To investigate the relationship between family support and stress levels in patients with Type II Diabetes Mellitus at the RSUD Bayu Asih inpatient unit. Methods. This study employed a cross-sectional design. Sampling was carried out using a quota sampling technique with totaling 55 individuals. Bivariate analysis used the chi-square test. Findings. There is a relationship between family support and stress levels in patients with Type II Diabetes Mellitus at the RSUD Bayu Asih inpatient unit, with the chi-square test yielding a p-value of 0.01 (a = 0.05). Implications. Majority of patients with Type II Diabetes Mellitus receive good family support; however, a significant proportion still experiences moderate levels of stress. The implications of these findings suggest that while family support is considered adequate, there remains room for improving the quality of this support, particularly in the context of stress management.